(untitled) (Journal of the College of Basic Education, 2019)
The research aims to build educational units for planning and colors according to "Modern Art Schools", the current research adopted the descriptive-analytical method as being the most appropriate scientific curricula to achieve the objectives of his research, as the research community consists of the characteristics and techniques of modern art schools as they represent the educational experience that will be included in the curriculum Proposed for the subject of planning and colors within the program of preparing the university teacher in the Department of Art Education - College of Basic Education - University of Mustansiriya for the year 2017 - 2018, where the number of technical schools (13) schools emerged between the period 1864-1936, the researchers chose a purposive sample Of technical schools b Gott (3) schools are (impressionism - expressive - Cubism). The researchers designed an analysis tool for the works of art performed by the artists of modern art schools, which included the most important features and characteristics of these schools and the researchers used the Cooper equation to obtain the reliability and reliability of the analysis tool and experts. The most important findings of the current research are: Impressionist artwork was adopted in the follow-up of the change of color value reflected on the surfaces of visuals associated with moving relative time, which caused a relative local displacement within the thought of modernity, which corresponds to the displacement of the surfaces and transformed the actual work of art into a formal abstraction according to various styles